Pengembangan sumber daya manusia untuk meningkatkan perekonomian daerah di provinsi Kalimantan Tengah - Atsari Sujud; Muhammad Ivan (Jurnal Riset Manajemen dan Bisnis, 2022)
On a regional scale, Central Kalimantan, which has human capital that dominates the labor market in both the formal and informal sectors, is faced with low skills to face the digitalized job market, including the tourism industry and MSMEs. With a touch of the creative economy, the market could be more active due to the inability to package tourism products. The upstream human capital, namely high school/vocational high school/equivalent graduates, needs to prepare in a planned way to face the job market. Governance factors are becoming increasingly important, along with the vision of regional heads, local government organizations (OPD), and private companies through CSR. Moreover, digital business start-ups need to be considered by corporate to build human resource development management for SMK graduates that are integrated with the business and industrial world (DUDI).